Perfil epidemiológico, metabólico e de reações adversas cutâneas em pacientes com psoríase em uso de anti-TNF - Alves, Karine Paschoal Botelho (2019)
Tumor necrosis factor (TNF) is an important inflammatory cytokine in the pathogenesis of psoriasis and metabolic syndrome (MS). Patients with psoriasis have higher rates of MS; therefore, this population requires MS screening. In addition, TNF-inhibitor treatment often modifies the metabolic profiles of these patients.Aside from that, the use of anti-TNF is not free from adverse side effects.One of the most common side effect of using anti-TNF is skin reactions. There are many tools that assist dermatologists in evaluating the effectiveness of the anti-TNF treatment, as well as, tools that help toevaluate the patients’ quality of life following the course of treatment. The main evaluative tools are the PASI score (Psoriasis Area and Severity Index) and the DLQI score (Dermatology Life and Quality Index). For the purpose of this study, we have evaluated 83 patients with psoriasis who were using anti-TNF. We analyzed the sample’s demographic characteristics, prevalence of metabolic syndrome, as well as the occurrences of cutaneous adverse reactions in relation to this therapy. In addition, we intended to verify whether the use of TNF inhibitors had influencedchanges in the metabolic parameters within the sample. The mean age and disease duration of the patients were 48±11 and 16±9 years, respectively. Most patients were men (61.5%). The prevalence of MS was 36%, and high rates of abdominal obesity (59%) and overweight (82%) were observed. Anti-TNF treatment significantly altered total cholesterol levels (195.5±36.17 vs. 183.5±41.23, p=0.04) and LDL levels (128.5±31.26 vs. 113±36.31, p=0.04).Overall, the use of anti-TNF treatment has shown a decreasein the PASI score, and we have observed a direct linear relationship between the PASI score and the DLQI score. Within the sample population, we have found a total of thirtycases of adverse skin reactions, 63,3% of which were diagnosed fungi skin infections (tinea, pityriasis versicolor, and candidiasis). The percentage of these reactions were 36,67%, 16,67%, and 10%, respectively.None of the patients have discontinued the therapy due to the cutaneous side effects. To conclude, the use of anti-TNF can positively improve the metabolic profile of patients with psoriasis, and the majority of skin side effects are mild, and do not require the suspension of the therapy.